The road to Blair Mountain : saving a mine wars battlefield from king coal - Keeney, Charles Belmont (West Virginia University Press, 2021)
"In 1921 Blair Mountain in southern West Virginia was the site of the country's bloodiest armed insurrection since the Civil War, a battle pitting miners led by Frank Keeney against agents of the coal barons intent on quashing organized labor. It was the largest labor uprising in US history. Ninety years later, the site became embroiled in a second struggle, as activists came together to fight the coal industry, state government, and the military-industrial complex in a successful effort to save the battlefield-sometimes dubbed "labor's Gettysburg"--Destruction by mountaintop removal mining. A success story for historic preservation and environmentalism, it serves as an example of how rural, grassroots organizations can defeat the fossil fuel industry"--